D-Penicillamine Induced Degenerative Dermopathy in a Patient with Wilson Disease - Rui Pedro Santos; Joana Gomes; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
D-penicillamine induced degenerative dermatosis include, among others, elastosis perforans serpiginosa, and pseudo- -pseudoxanthoma elasticum. Elastosis perforans serpiginosa is a rare perforating disease characterized by transepidermal elimination of abnormal elastic fibers. This condition can be idiopathic, reactive or induced by D-penicillamine, commonly used for the treatment of Wilson disease, cystinuria, rheumatoid arthritis or systemic sclerosis. Cutaneous manifestations resembling pseudoxanthoma elasticum but lacking familiar history and ABCC6 mutations have been identified as a D-penicillamine induced dermopathy and called pseudo-pseudoxanthoma elasticum. The authors present a 17-year-old caucasian female treated for several years with D-penicillamine for Wilson disease who developed asymptomatic papules, some hyperkeratotic skin-colored and other soft and yellowish, on the cervical region and face. Histopathology showed transepidermal elimination of numerous, branched, sawtooth-like elastic fibers. These findings suggested a D-penicillamine induced dermopathy and the authors considered the diagnosis of both elastosis perforans serpiginosa and pseudo- -pseudoxanthoma elasticum in the same patient. The drug was switched to zinc acetate. No newer lesions appeared thereafter but previous lesions persisted at the 1 year follow-up.